Uniqlo Fashion Brands: The Role of Brand Love and The Impact of Brand Personality on Consumer Behavior (Jurnal Manajemen Bisnis, 2022)
This study investigates the effect brand personality and brand love on brand loyalty, positive word of mouth, resistance to negative information, willingness to pay more, self-disclosure and active engagmenet in fashion brand uniqlo. Data processing in this research using Structural Equation Model (SEM) and AMOS operated by Statistical Package for Social Sciences (SPSS) versi 18 dan Lisrel 8.7 for windows software. Respondents were taken from customers of fashion brand unuqlo in the city of Surabaya who had bought and use the brand's products.